Record of Insect Pests of Medicinal and Aromatic Plants in Jammu & Kashmir - Mathur, A. C.; Srivastava, J. B. (Indian Forester, 1967)
Fifty-two different species of insect pests attacking fifty-seven medicinal and aromatic plants both cultivated and wild have been recorded in Jammu & Kashmir during 1961-66. The paper gives the details of food plants and stages responsible for the damage to the plants.